The Epidemiology of Psoriatic Arthritis Over Five Decades: A Population‐Based Study. Issue 10 (14th August 2021) - Karmacharya, Paras; Crowson, Cynthia S.; Bekele, Delamo; Achenbach, Sara J.; Davis, John M.; Ogdie, Alexis; Duarte‐García, Alí; Ernste, Floranne C.; Maradit‐Kremers, Hilal; Tollefson, Megha M.; Wright, Kerry
Abstract : Objective: To determine the incidence of psoriatic arthritis (PsA) in a US population and describe trends in incidence and mortality over 5 decades. Methods: The previously identified population‐based cohort that included Olmsted County, Minnesota residents ≥18 years of age who fulfilled PsA criteria during 1970–1999 was extended to include patients with incident PsA during 2000–2017. Age‐ and sex‐specific incidence rates and point prevalence, adjusted to the 2010 US White population, were reported. Results: There were 164 incident cases of PsA in 2000–2017 (mean ± SD age 46.4 ± 12.0 years; 47% female). The overall age‐ and sex‐adjusted annual incidence of PsA per 100, 000 population was 8.5 (95% confidence interval [95% CI] 7.2–9.8) and was higher in men (9.3 [95% CI 7.4–11.3]) than women (7.7 [95% CI 5.9–9.4]) in 2000–2017. Overall incidence was highest in the 40–59 years age group. The incidence rate was relatively stable during 2000–2017, with no evidence of an overall increase or an increase in men only (but a modest increase of 3% per year in women), compared to 1970–1999 when a 4%‐per‐year increase in incidence was observed. Point prevalence was 181.8 per 100, 000 population (95% CI 156.5–207.1) in 2015. The percentage of women among those with PsA increased from 39% in 1970–1999 and 41% in 2000–2009 to 54% in 2010–2017 ( P = 0.08). Overall survival in PsA did not differ from the general population (standardized mortality ratio 0.85 [95% CI 0.61–1.15]). Conclusion: The incidence of PsA in this predominantly White US population was stable in 2000–2017, in contrast to previous years. However, an increasing proportion of women with PsA was found in this study.